2015
DOI: 10.1371/journal.pone.0124041
|View full text |Cite
|
Sign up to set email alerts
|

The Missed HIV-Positive Children of Ethiopia

Abstract: ObjectiveAs elsewhere, due to scarcity of data and limited awareness of HIV infection, especially in older children, the HIV epidemic among Ethiopian children appears neglected in national programs (children ART coverage is of only 12% in 2013). This paper estimates the country burden of HIV in older children and investigates the prevalence of HIV in orphans and vulnerable children (OVC) households.Design/MethodsWe analyzed national HIV data for Ethiopia, using Spectrum/ Estimation and Projection Package (EPP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 11 publications
0
23
1
Order By: Relevance
“…However, recent research has found that HIV infection progresses slowly among some infants and a substantial proportion of HIV positive survive to adolescence and beyond. 13,14 Moreover, recent research in Kenya 15 and Ethiopia 16 has found substantial HIV prevalence for older children (under age 15), the majority of whom were presumably not infected through sexual transmission due to low rates of sexual activity for these age groups. In addition, an intervention to reduce HIV among Zimbabwean adolescents had no impact on orphan HIV disparities, leading the authors to suggest that excess risk among orphans is likely due to maternal transmission.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…However, recent research has found that HIV infection progresses slowly among some infants and a substantial proportion of HIV positive survive to adolescence and beyond. 13,14 Moreover, recent research in Kenya 15 and Ethiopia 16 has found substantial HIV prevalence for older children (under age 15), the majority of whom were presumably not infected through sexual transmission due to low rates of sexual activity for these age groups. In addition, an intervention to reduce HIV among Zimbabwean adolescents had no impact on orphan HIV disparities, leading the authors to suggest that excess risk among orphans is likely due to maternal transmission.…”
mentioning
confidence: 99%
“…Due to the predominant focus on sexual transmission, HIV testing efforts are typically not directed towards this population. 16 As a result, many of these HIV positive children are undiagnosed and not linked to treatment. 15,16 As these “missing children” mature into adolescents, they may alter the future course of the HIV epidemic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is not only consistent with prior research but adds to argument for consistently using PSWCHW in programming service delivery for vulnerable children. This finding helps support communitybased health care research that has shown PSWCHW help to address a wide range of issues for the vulnerable population, from psychosocial support to adherence to HIV treatment for the population they serve (Pegurri et al, 2015;Taylor & Kvalsvig, 2008) PSWCHW were able to address issues of adherence to health care and to provide supportive mental health interventions, sexual health education, and ways to navigate cultural social spheres to ensure community needs were served (Beard, 2005;Friedman, 2005;Hermann et al, 2009;Pegurri et al, 2015). Their community knowledge helped them use individuals' and family strength to assist them (Heath et al, 2008).…”
Section: Discussionmentioning
confidence: 52%
“…They have helped to address a wide range of issues, including psychosocial support, adherence to HIV treatment, and nutrition education to support early childhood development (Taylor & Kvalsvig, 2008). Clinical adherence, mental health, sexual health and social spheres must be included in the provision of care for children living with HIV (Pegurri et al, 2015). Social work and public health care intersect when supporting households at the community level (Beard, 2005;Friedman, 2005;Hermann et al, 2009).…”
Section: Para-professionals In Practice and Implications For Social Wmentioning
confidence: 99%